Association of learning setups to the nutritional status of pre-adolescent children from a selected school district in Quezon City - Castro, Brylle Gabriel R.; Manzanares, Ma. Kyla Angelica C.; Loyola, maverick Lance N. (College of Home Economics, University of the Philippines Diliman, 2023)
A child’s learning environment has been known to play a role in determining nutritional outcomes (Nguyen et al., 2018). This study investigated this aspect of children's health related to the changes in their food consumption and nutritional status brought about by the COVID-19 pandemic. The researchers determined the association of learning setups to the nutritional status of pre-adolescent children from selected elementary schools in District IV, Quezon City. The study adapted the correlational research design where participants were randomly chosen among 10-to 12-year-old Filipino children from selected elementary schools in District IV of Quezon City. Anthropometric measurements were conducted remotely via a self-administered questionnaire and were evaluated according to the children’s BMI-for-Age and Height- for-Age. Dietary assessment, meanwhile, included assessing the adequacy of carbohydrates, protein, fat, iron, vitamin A, and zinc in pre-adolescent children. Consumption adequacy was based on the acquired 2-day non-consecutive food record that was self-administered by the children and parents. Percent adequacy based on the Philippine Dietary Reference Intake (PDRI) was used to assess dietary intake. The anthropometric data gathered were processed using the WHO child growth standards and the AnthroPlus software. Dietary assessment was processed using the Philippine Dietary Reference Intake 2015. Using chi-square analysis, the study concluded that there is no significant association between learning setups with the height-for-age classification (p=0.723), BMI-for-age classification (p=0.329), carbohydrate intake adequacy (p=0.170), fat intake adequacy (p=0.325), iron intake adequacy (p=0.071), vitamin A intake adequacy (p=0.588), and zinc intake adequacy (p=0.419). Furthermore, the learning setup was found to be statistically associated (p=0.015) with protein intake adequacy, particularly with the Blended Learning (BL) setup showing better outcomes than the Face-To-Face (FTF) setup. Further studies can investigate the feeding practices done in the BL setup that could be translated to the FTF setup to attain strategies to ensure that pre-adolescent children can attain adequate protein intake during and after pandemics.